The role of financial technology in improving customer services: Case study of Iraqi Rafidain Bank (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aims to know the role of financial technology, which means using modern technological methods to provide financial services well, this is in order to improving customer services, through a case study of Rafidain Bank in Iraq. The descriptive analytical approach was relied upon, and the questionnaire was relied upon as a tool for collecting data, and it was distributed to 116 workers at Rafidain Bank in Iraq. The study, and the data were analyzed based on the statistical analysis program SPSS version 25, and the study reached the following results: There is a significant role for financial technology in improving customer services. There are no significant differences between the average of the sample answers and the average of scale (3) regarding the role of financial technology in improving customer services according to the experience variable. Based on these results, the researcher presented the following recommendations: Activating the role of technology and related techniques in the Iraqi Rafidain Bank by holding training courses for employees on using the latest banking technological programs, and enhancing customer service in the Iraqi Rafidain Bank by improving services and linking them to contemporary technologies that save time and effort. With the aim of maintaining existing customers and attracting new ones.